Gastric Carcinoid and Obesity: Association or Coincidence? Report of Two Cases and Literature Review - Obaid Al-Harbi; Mustafa Shakir; Nabeel Al-Brahim (Case Reports in Gastrointestinal Medicine)
Bariatric surgery is a prevalent procedure due to the high incidence of obesity and comorbidities. Upper gastrointestinal endoscopy is one of the procedures used to evaluate the patient before surgery. However, its role is questionable. The incidental findings during endoscopy are variable including inflammatory diseases, and ulcers, and epithelial and stromal tumors. Herein a report of two obese sisters with incidental gastric carcinoids was diagnosed in prebariatric surgery endoscopy. Case Summary. 35- and 41-year-old female patients presented with obesity and BMI of 102 and 46 kg/m2, respectively. Both patients underwent upper gastrointestinal endoscopy as part of presurgical evaluation. Multiple polyps were indentified in both patients, and biopsy was taken. Histological examination revealed tumors that were formed by nests of epithelial cells. The cells have eosinophilic cytoplasm and monomorphic nuclei, typical morphology of neuroendocrine tumors. Conclusions. (1) Upper gastrointestinal endoscopy is an important procedure for prebariatric surgery evaluation. (2) Gastric carcinoid is a rare tumor with higher incidence among obese patients.